Uma resposta da Pedagogia Inaciana à Sociedade do Cansaço: a utilização dos smartphones em sala de aula - Teixeira, Mateus Barradas (Universidade do Vale do Rio dos Sinos, 2025)
The present article proposes an Ignatian Pedagogy response to the so-called Society of Tiredness, especially in the context of excessive smartphone use in educational settings. Beginning with an analysis of Law 15.100/25, which regulates the use of electronic devices in educational institutions, the text investigates the impacts of this legislation on Colégio Anchieta in Nova Friburgo. Drawing on Byung-Chul Han’s reflections on hyperproductivity, distraction, and the loss of contemplative experience, the article arguesthat structuring elements of Ignatian pedagogy — such as the Spiritual Exercises, Magis, Cura Personalis, and Critical Innovation — offer pathways to resist the logic of performance, predominantly characterized by exhausting patterns in which there is no space to stop, pause, or conclude. The methodology includes documentary and hermeneutical analyses, articulating critical theory with a case study. It concludes that Ignatian pedagogy offers a formative alternative to confront the challenges imposed by digital culture and neoliberal logic in today’s educational environment.
Keywords: Pedagogia Inaciana; Sociedade do Cansaço; Smartphones; Educação contemporânea; Formação integral; Ignatian pedagogy; Burnout society; Contemporary education; Integral formation